Scoping review of impact of digital transformation on business processes - Lysenko, Sergii (UKEY Consultancy & Publishing, 2023)
Over the past decades, and in particular since COVID-19 pandemic, digital transformation has covered more and more areas in business and management. Digital transformation poses new challenges for scientists, especially when assessing the impact of digital transformation on business processes. The scientific research is devoted to the analysis of existing approaches to measuring the effect of the implementation of digital transformation in the system of corporate governance in terms of compliance with the principles of sustainable development. This article conducted research on scientific articles from 2019 to 2023 years to demonstrate the relevance of topics in the field of digital transformation of management and business processes. The research method is based on a comprehensive search method using an iterative process, which is guided by the requirement to identify all relevant literature (published and unpublished) suitable to answer the main question: the impact of digital transformation on business processes. The key criteria for the search were words and phrases: digital transformation, business processes, management, model, processes, as well as various categories by authors, number of articles and their citations. The implementation strategy of modern digital technologies and initiatives should be based on a systematic approach to measurement, analysis, and improvement of the organization's business processes for sustainable development. The ways and directions of implementing digital business process tracements directly affect the effectiveness and success in general. The result suggests future opportunities in this widespread field and thereby highlights the most influential and unique research in the field.
Keywords: digital transformation; business processes; management; impact assessment; model; evolution